Analisis Kesesuaian dan Daya Dukung Kawasan Ekowisata Mangrove di Pulau Osi - Sari Sari; Renoldy L. Papilaya; Adnan Affan Akbar Botanri (ELASTICITY: Journal of Applied Engineering Science, 2024)
Osi Island is included in the leading tourist destinations of Western Seram Regency. The island has a major attraction, namely a mangrove forest along a wooden bridge with a length of 1,300 meters. The problems in this study are that there is no clean water, some facilities are not good, access in ecotourism areas such as bridges and trails are starting to have holes. The purpose of this study is to determine the existing condition of mangrove ecotourism, as well as to analyze the value of suitability and carrying capacity of mangrove ecotourism areas. This study uses descriptive analysis methods, visitor perception analysis, suitability analysis and area carrying capacity analysis. The results obtained are that the existing condition of the Osi Island mangrove forest ecotourism has cool forest conditions along the bridge and clean sea views, but the access (trails and bridges) to Osi Island is still damaged and there are supporting facilities and infrastructure that are already available. The total score of the results of the mangrove ecotourism condition of Osi Island is included in the S2 category (Appropriate), with a total score of 68 and a tourism suitability index of 78%, meaning that it can be used for ecotourism activities and the carrying capacity of the mangrove ecotourism area on Osi Island is 409 people per day